Replication of the Petalaindera boat: a comparative study of optical sensors and computer vision technologies for digital heritage practice in Malaysia - Md. Sharif, Harlina; Hazumi, Hazman; Meli, Rafiq Hafizuddin (IIUM Press, 2018)
3D reconstruction from images has undergone a massive revolution in recent years. Despite this rapid development, progress in Malaysia pertaining to digital heritage is rather slow. Documentation of 3D cultural assets is still very much reliant upon conventional techniques such as measured drawings and manual photogrammetry. There is very little progress towards exploring new methods or advanced technologies to convert 3D cultural assets into 3D visual representation and visualization models that are easily accessible for information-sharing. Shortage of expertise in many levels of digital practice and the general perception that 3D digital documentation is costly and requiring high investments further hampers digitization efforts. This study investigates the potential of using image-based applications using open-source software and web services to replicate the Petalaindera boat, currently being kept at the Royal National Museum. This artefact has been selected due to its size, fragility, complexity, and intricacy of design. The objective of the study is to assess the accuracy of 3D models generated by computer vision automated web-based applications (such as Autodesk 123D Catch) and compare the output to 3D models produced by optical technologies using multi-image photogrammetry and commercial 3D scanner. The web-based application enables the automatic generation of 3D point clouds or surface models (as 3D polygons) with photo-realistic texture from image data thus represent an efficient alternative to expensive terrestrial laser scanning systems for the as-built documentation of 3D objects in cultural heritage. The output of the study will be in the form of 3D replication of the Petalaindera, using 3D print technology. By evaluating the efficiency of such systems and their suitability to be adopted in digital heritage practice in Malaysia, this study explores cost-effective methods that could provide fundamental guidelines on the best practice approach for digital heritage in Malaysia.